Sustainable supply chain performance measurement a case study of the sugar industry - Apichat Sopadang (2018)
© IEOM Society International. The purpose of this paper is to introduce a framework to measure the sustainable performance of supply chains. The supply chain stakeholders in this study are suppliers, a manufacturer, customer and the surrounding community. The proposed sustainable supply chain performance measurement consists of three dimensions with 14 indicators. In order to assess overall sustainability of the studied supply chain, a composite index is developed to combine all indicators to reflect the sustainability performance of the supply chain. The case of the sugar industry in Thailand is selected as an illustrative case. There are 4 steps to create the composite index which are (1) measuring value (2) normalization method (3) weighting of indicators (4) aggregation method. The numerical example, based on obtained data of the Thai sugar industry, is provided in order to explain how to calculate the composite index. The findings show that the overall sustainable supply chain score of the manufacturer is 55.61% while suppliers, customers and the community, achieved a composite index score of 80.97% and 75.00% respectively. The major contribution of this paper is the development of sustainable supply chain indicators between supply chain stakeholders and an approach to measure overall sustainable supply chain performance via the development of a composite index.